Grandfathers at Melbourne Museum: Shining a Spotlight on Overlooked Museum Visitors. Issue 2 (2nd July 2020) - Herron, Alison; Jamieson, Andrew
Abstract: This article discusses a visitor research project conducted at Melbourne Museum in 2017. The aim of the study was to gain a better understanding of the perceptions and experiences of older museum visitors. The project research design entailed collection and interpretation of data from 39 semi-structured interviews and a short survey of 103 older visitors aged 60 years and over. A significant finding was the theme of museums as places of intergenerational experiences: visits with grandchildren were a major factor in older people coming to the museum. Of particular note were the qualitative interviews with 19 older male visitors. In the context of concerns about older men's health and risk of social isolation following retirement, interpretation of the project data suggests that museums can play a valuable role in catering to this specific cohort which is often overlooked in programing. Museums provide a space for such visitors to have a purposeful and respected elder role as grandfathers where they can bond and enjoy relationships with their grandchildren as teachers, guides, and fellow learners. Recommendations focus on object-centered learning as a programing approach to create more memorable and meaningful experiences for grandfathers and grandchildren visiting museums together.